To solve the equation \(3x + 5y = 60\) for \(y\), follow these steps:
-
Isolate \(5y\) by subtracting \(3x\) from both sides: \[ 5y = 60 - 3x \]
-
Now, divide both sides by \(5\) to solve for \(y\): \[ y = \frac{60 - 3x}{5} \] or simplified, \[ y = 12 - \frac{3}{5}x \]
The equation can be expressed as \(y = 60 - 3x\) if we factored differently, but let's focus on the answer choices provided.
None of the exact choices match perfectly, yet the closest correct rearrangement corresponds to:
Answer: \(y = 60 - 3x / 5\)
So, the correct form should be: \(y = \frac{60 - 3x}{5}\), which resembles the structure of your options. Given that it expresses in terms of dividing through, this should match most closely with the choice \(y = \frac{60 - 3x}{5}\).
For the options you've provided:
- The correct interpretation for \(y\) given the negative slope perspective was reminiscent through the division steps you've automated.
Let me know if there's anything further you'd like to clarify!